Simulating agricultural land rental markets by combining agent-based models with traditional economics concepts: The case of the Argentine Pampas. (September 2015) - Bert, Federico; North, Michael; Rovere, Santiago; Tatara, Eric; Macal, Charles; Podestá, Guillermo
Abstract: Land exchange through rental transactions is a central process in agricultural systems. The land tenure regimes emerge from land transactions and structural and land use changes are tied to the dynamics of the land market. We introduce LARMA, a LAnd Rental MArket model embedded within the Pampas Model (PM), an agent-based model of Argentinean agricultural systems. LARMA produces endogenous formation of land rental prices. LARMA relies on traditional economic concepts for LRP formation but addresses some drawbacks of this approach by being integrated into an agent-based model that considers heterogeneous agents interacting with one another. PM-LARMA successfully reproduced the agricultural land tenure regimes and land rental prices observed in the Pampas. Including adaptive, heterogeneous and interacting agents was critical to this success. We conclude that agent-based and traditional economic models can be successfully combined to capture complex emergent land tenure and market price patterns while simplifying the overall model design. Highlights: LARMA is a land rental market model with endogenous rental price formation. LARMA is embedded into the Pampas agent-based model (PM). LARMA combines traditional economics concepts with agent-based modeling. PM-LARMA successfully reproduces land tenure patterns and rental price dynamics. We discuss the advantages of combining approaches for modeling land rental markets.